2011
DOI: 10.1142/s1758825111001226
|View full text |Cite
|
Sign up to set email alerts
|

Wall Shear Stress in a Subject Specific Human Aorta — Influence of Fluid-Structure Interaction

Abstract: shear stress (WSS) has been correlated to the development of atherosclerosis in arteries. As WSS depends on the blood flow dynamics, it is sensitive to pulsatile effects and local changes in geometry. The aim of this study is therefore to investigate if the effect of wall motion changes the WSS or if a rigid wall assumption is sufficient. Magnetic resonance imaging (MRI) was used to acquire subject specific geometry and flow rates in a human aorta, which were used as inputs in numerical models. Both rigid wall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
106
4
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(128 citation statements)
references
References 33 publications
10
106
4
4
Order By: Relevance
“…This can be seen in the results for TAWSS and OSI, where the prescribed wall motion simulations yield very similar results. This is in line with a previous study [11] where it was concluded that the time-averaging the WSS parameters effectively filters out any temporal effects. On the other hand, the instantaneous WSS magnitude is affected by the wall motion: at peak flow rate both rigid wall cases result in higher WSS values compared to the three cases with prescribed wall motion.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This can be seen in the results for TAWSS and OSI, where the prescribed wall motion simulations yield very similar results. This is in line with a previous study [11] where it was concluded that the time-averaging the WSS parameters effectively filters out any temporal effects. On the other hand, the instantaneous WSS magnitude is affected by the wall motion: at peak flow rate both rigid wall cases result in higher WSS values compared to the three cases with prescribed wall motion.…”
Section: Discussionsupporting
confidence: 93%
“…However, these models are based on several assumptions including the wall thickness, the stress-strain relationship of the arterial wall, homogeneous material properties, the impact of surrounding tissue and organs, and pressure and mass wave reflections from arterial bifurcations and branches outside the computational domain. Depending on desired model complexity and available data on the subject/patient, the wall can be modeled using either a linear [11] or non-linear [12,13] material model. However, to obtain an accurate wall deformation for non-linear material models, the residual stresses, that are present even in a non-pressurized aortic wall, must be accounted for.…”
Section: Introductionmentioning
confidence: 99%
“…adopted emphasizes that the PC-MRI flow measurements-derived uncertainty is an important source of uncertainty. This is of utmost importance considering that it is non-linearly related with other uncertainties intrinsic in modeling assumptions such as aortic wall distensibility (Lantz et al 2011;Brown et al 2012), outflow boundary conditions (Gallo et al 2012), blood rheological properties (Liu et al 2011), etc. As a consequence, the global effect cannot be neglected when looking at model reliability.…”
Section: Discussionmentioning
confidence: 99%
“…This model can also be applied in the case of turbulence with low Re value and in flow separation regions (vicinity of valve cusps, vascular divisions); hence its use in, e.g., aortic blood flow simulations [24]. Based on our own durability studies, computer models of the geometry of an aorta with elastic walls and mobile valve cusps were prepared.…”
Section: Methodology Of Experimental and Numerical Researchmentioning
confidence: 99%